PENGARUH PEMAHAMAN PERATURAN PAJAK, TARIF PAJAK, LINGKUNGAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PENGGUNA E-COMMERCE (Universitas Islam Malang, 2019)
ABSTRACT This study aims to determine the effect of understanding tax regulations, tax rates, environment and taxpayer awareness of taxpayer compliance with E-Commerce users. This study design used qualitative research. The selection of samples using simple random sampling method, as many as 100 taxpayer respondents. The results of this study prove that understanding tax regulations, tax rates, environment and awareness of taxpayers simultaneously has a significant positive effect on taxpayer compliance with e-commerce users. Moreover, understanding tax regulations, tax rates, the environment partially does not affect the taxpayer compliance of e-commerce users, while the awareness of taxpayers partially has a significant positive effect on the taxpayer's e-commerce user compliance.Keywords : Understanding of Tax Regulations, Tax Rates, Taxpayer Environment, Taxpayer Awareness.